2021
DOI: 10.1155/2021/6694689
|View full text |Cite
|
Sign up to set email alerts
|

Study on Wellbore Stability and Failure Regions of Shale considering the Anisotropy of Wellbore Seepage

Abstract: The hard and brittle shale formation is prone to collapse and instability, and the penetration of drilling fluid along the bedding reduces the mechanical properties of rock near the borehole wall, resulting in serious downhole accidents. Therefore, in this paper, the geomechanical parameters of the reservoir in the Longmaxi formation of Jiaoshiba were determined by field hydraulic fracturing and laboratory experiments. Then, the stress distribution model of borehole wall under the condition of underbalanced se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 38 publications
(61 reference statements)
0
5
0
Order By: Relevance
“…Figure 12 shows the frequency distribution of the angles β w at which the peaks of the mud weight occur. The distribution of the angles β w was calculated at different far field stresses (R = 1-1.5), pore fluid pressures (8 MPa,11 MPa and 15 MPa) and inclination of the weakness planes Figure 11c shows the percentage change in SG with the variation of the far field stresses ΔR (at constant pore fluid pressure pf = 11 MPa). The change in R from 1.1 to 1.5 corresponds to ΔR = +36% and the change in R from 1.1 to 1.25 corresponds to ΔR = +14%.…”
Section: Influence Of the Far Field Stresses And Pore Fluid Pressure ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 12 shows the frequency distribution of the angles β w at which the peaks of the mud weight occur. The distribution of the angles β w was calculated at different far field stresses (R = 1-1.5), pore fluid pressures (8 MPa,11 MPa and 15 MPa) and inclination of the weakness planes Figure 11c shows the percentage change in SG with the variation of the far field stresses ΔR (at constant pore fluid pressure pf = 11 MPa). The change in R from 1.1 to 1.5 corresponds to ΔR = +36% and the change in R from 1.1 to 1.25 corresponds to ΔR = +14%.…”
Section: Influence Of the Far Field Stresses And Pore Fluid Pressure ...mentioning
confidence: 99%
“…In these depleted fields, new wellbores must be drilled for gas injection operations. Consequently, drilling operation in shale is still a matter of concern [8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Also stated that deviated wells may require side-tracks to mitigate instability which means higher well costs [20]. studied effects of deviation angle and pore pressures in wellbore instability and found that it is insufficient to rely only on pore pressure to design the stable mud weight window [21].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Proposed two models of collapse pressure calculation and well-cycle instability area. The condition of underbalanced seepage flow and the rock strength anisotropy were taken into consideration in both models [22]. Presented a non-linear model that is 'thermo-chemo-poroelastic' to study the effect of distinct types of gradients on the distribution of stress and pore pressure in the wellbore.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Frash et al [27] studied the apparent permeability characteristics induced by shear fractures of bedding shale under high triaxial stress and the relationship between frac-ture geometry and apparent permeability through shear tests. Other scholars [28][29][30] have studied the stability and collapse area of shale boreholes considering the mechanical properties of natural bedding geological bodies and weak structural planes, which provide guidance and recommendations for drilling techniques in permeable, brittle, and hard bedding shale. Zhang et al [31] analyzed the influence of water activity on shale and found that the effect of anisotropy on the compressive strength of shale decreases with the increase in water content, which is the main factor controlling the mechanical behavior.…”
Section: Introductionmentioning
confidence: 99%